Atomizing Spray Systems for Application of Edible Coatings - Osorio-Lira, F; Andrade-Pizarro, R (2012)
The use of edible coatings on fresh and processed food products as a means of extending shelf life by preventing or delaying spoilage, providing a partial barrier to moisture, oxygen, and carbon dioxide, improving the mechanical handling properties, and even as carriers of many functional ingredients, is rapidly growing. Edible coatings can be applied by different methods such as panning, fluidized bed, dipping, and spraying. This review presents and discusses some aspects of the application of edible coatings on food products using spraying, which is the most commonly used technique for applying food coatings and to obtain uniform layers. © 2012 Institute of Food Technologists®.